2020
DOI: 10.18632/oncoscience.497
|View full text |Cite
|
Sign up to set email alerts
|

Cracking the riddle of dedifferentiated liposarcoma: is EV-MDM2 a key?

Abstract: Dedifferentiated liposarcoma (DDLPS) is molecularly characterized by wt p53 and MDM2 gene amplification causing MDM2 protein overproduction , the key oncogenic process in DDLPS. Commonly located in fat-bearing retroperitoneal areas, almost 60% of DDLPS patients undergo multifocal recurrence, typically amenable to palliative treatment only, and occasionally develop distant metastasis. These factors lead to an abysmal 10% 10 year overall survival rate. Tumor cell-derived extracellular vesicles (EVs) can facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Previous research has shown that microfluidic devices can better preserve extracellular vesicle (EV) cargo during the isolation of particles ( Perut et al, 2019 ; Casadei et al, 2021 ), providing us with a unique opportunity to gain insights into the mechanisms underlying DDLPS recurrence events. Previously, we have observed high levels of MDM2 DNA in EVs derived from DDLPS patient serum and cell lines, which was transferable to preadipocytes at the microenvironment level ( Casadei et al, 2019 ; Casadei and Pollock, 2020 ). Building on this observation, we hypothesize that the DDLPS microenvironment plays a crucial role in DDLPS recurrence.…”
Section: Discussionmentioning
confidence: 86%
“…Previous research has shown that microfluidic devices can better preserve extracellular vesicle (EV) cargo during the isolation of particles ( Perut et al, 2019 ; Casadei et al, 2021 ), providing us with a unique opportunity to gain insights into the mechanisms underlying DDLPS recurrence events. Previously, we have observed high levels of MDM2 DNA in EVs derived from DDLPS patient serum and cell lines, which was transferable to preadipocytes at the microenvironment level ( Casadei et al, 2019 ; Casadei and Pollock, 2020 ). Building on this observation, we hypothesize that the DDLPS microenvironment plays a crucial role in DDLPS recurrence.…”
Section: Discussionmentioning
confidence: 86%
“…The diagnostic and prognostic challenges prompted us and other researchers to study mechanisms of progression of this disease and to explore the use of circulating biomolecules like micro‐ribonucleic acids (miRNAs) and deoxyribonucleic acid (DNA) that could serve as potential biomarkers for early stage detection and are accessible through bodily fluids (He et al., 2015; Jin et al., 2012). Past work has shown that miR‐25, miR‐92, and MDM2 DNA may be associated with the development and progression of DDLPS (Casadei & Pollock, 2020; Casadei et al., 2017, 2019). Moreover, it was discovered that these miRNAs and DNA serve as cargo contained within extracellular vesicles (EVs), released from tumors and present in the circulatory system (Casadei & Pollock, 2020; Casadei et al., 2017, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Past work has shown that miR‐25, miR‐92, and MDM2 DNA may be associated with the development and progression of DDLPS (Casadei & Pollock, 2020; Casadei et al., 2017, 2019). Moreover, it was discovered that these miRNAs and DNA serve as cargo contained within extracellular vesicles (EVs), released from tumors and present in the circulatory system (Casadei & Pollock, 2020; Casadei et al., 2017, 2019).…”
Section: Introductionmentioning
confidence: 99%